Metabolic control of type I (insulin dependent) diabetes after pancreas transplantation. Issue 6494 (24th August 1985) - Pozza, G; Bosi, E; Secchi, A; Piatti, P M; Touraine, J L; Gelet, A; Pontiroli, A E; Dubernard, J M; Traeger, J
Abstract : A study was conducted of the circadian hormonal and metabolic patterns of 10 type I (insulin dependent) uraemic diabetic patients after pancreas and renal transplantation. A single 24 hour profile was obtained in each patient following as closely as possible his or her normal daily routine two to 15 months after transplantation. None of the patients were using insulin at the time of the study. Compared with a group of six normal subjects the transplant recipients had mildly raised blood glucose concentrations, hyperinsulinaemia between meals and at night, delayed postprandial insulin peaks, mild hyperketonaemia, and normal blood lactate and plasma glucagon concentrations. The findings showed that successful pancreas transplantation results in disappearance of the need for insulin and return to normal or near normal of the metabolic abnormalities of diabetes. The minor differences observed in comparison with normal hormonal and metabolic homoeostasis were probably due to intrinsic (reduced islet mass, denervation, peripheral hormone delivery) and environmental (immunosuppression, relatively impaired renal function) factors.